697 Binding of gamma-glutamyl transferase to toll-like receptor-4 allows tissue factor activation in monocytes. (8th December 2021) - Sanguinetti, Chiara; Scalise, Valentina; Neri, Tommaso; Celi, Alessandro; Pedrinelli, Roberto
Abstract: Aims: Gamma-glutamyl transferase (GGT) is well known to play a key role in the antioxidant processes, however, it also exerts pro-oxidant effects by activating NFkB, a redox-sensitive transcription factor key in the induction of tissue factor (TF) gene expression, the principal initiator of the clotting cascade. GGT may potentially modulate TF expression, an assumption verified by previous studies carried out in human peripheral blood mononuclear cell (PBMC). Quite importantly, TF expression in response to GGT stimulation was independent of its enzymatic properties since those experiments were conducted by using human recombinant (hr)GGT, a wheat germ-derived protein enzymatically inert because of missing post-translational glycosylation site. Thus, GGT may act through a cytokine-like mechanism although the precise determinants of its action and the receptor involved were not defined by those experiments. To assess whether GGT-induced TF stimulation is a consequence of binding to toll-like receptor (TLR)-4 and activation of NFkB, as suggested by results recently obtained in different experimental contexts. Methods: PBMCs obtained from healthy donors through a discontinuous Ficoll/Hystopaque density gradient and THP-1 cells, a human monocytic cell line derived from an acute monocytic leukaemia patient, were incubated with hrGGT (0.5 ng/μL for PBMCs and 1 ng/µL for THP-1). LPS-Rs (0.5 ng/µL for PBMCs and 1 ng/µL for THP-1), CLI-095 (3 × 10 −6 M) and BAY-11-7082 (10 −5 M) were used to block TLR-4 receptors, TLR4 signalling and NFkB respectively. TF protein concentration was determined by western blot analysis. TF pro-coagulant activity (PCA) was assessed through the use of Start Max coagulometer and results were expressed in pg/mL after calibration with a standard curve. HEK-Blue hTLR4-positive and HEK-Blue hTLR4-negative cells are used to evaluate the engagement of TLR4 by hrGGT. Results: hrGGT increased TF expression in both PBMCs (PCA from 110 ± 70 to 510 ± 43, n  = 7, P  < 0.01) and THP-1 cells (PCA from 170 ± 64 to 460 ± 80, n  = 15, P  < 0.001), result confirmed by western blot. In PBMCs GGT-induced TF stimulation was antagonized by LPS-Rs (PCA: −72 ± 17% n  = 4, P  < 0.01) a TLR-4 antagonist, CLI-095 (PCA: −74 ± 34%, n  = 7, P  < 0.001) a TLR-4 intracellular antagonist and BAY-11-7082 (PCA: −71 ± 32%, n  = 7, P  < 0.001), a NF-kB inhibitor. Similar results were obtained in THP-1 cells (LPS-Rs: −76 ± 15%, n  = 6, P  < 0.01; CLI-095: −100 ± 6, 6 %, n  = 6, P  < 0.01; BAY-11-7082: −100 ± 2, 1%, n  = 6, P  < 0.01). hrGGT activates NFkB in hTLR4-positive HEK cell lines while does not induces effect in TLR4-negative HEK cell lines. Conclusions: These data confirm the cytokine-like activity of GGT and its procoagulant effect in PBMCs and THP-1 cells. Furthermore, it is highlighted for the first time the possible role of TLR-4 as the receptor of GGT and NFkB as the involved signal transduction pathway. The GGT-TLR-4 link may provide an explanation to the consistent association between circulating GGT levels and increased risk of acute thrombotic events as well as to the involvement of GGT in the morbid evolution of the silent atherosclerotic plaque in which GGT colocalizes with monocytes and foam cells, the prime sources of TF within the plaque.